ナンキョク ノ ツウシン カイギ ト ショウライ ノ テンボウ - 河原, 猛夫; カワハラ, タケオ; KAWAHARA, Takeo (国立極地研究所, 1970)
P(論文) The commencement of the Antarctic Telecommunications by SCAR groups is briefly reviewed first, and the report of the Second Antarctic Treaty Meeting on Telecommunications, held at Buenos Aires in September 1969, is given. The 9 proposals, decided at the meeting, will supersede the Recommendations of the First Antarctic Telecommunications Meeting in 1963, upon approval at the Sixth Antarctic Treaty Consultative Meeting in Tokyo this year. In accordance with the requests presented by WMO, the meeting agreed to revise the coordinated schedule for speedy handling of meteorological raw data from the observing stations to WMC and AMC, by transmitting those traffics through the circuits and the routes existing and requested or preferred by the parties concerned. The establishment of AMC at 5 Antarctic bases results inevitably in the remarkable increase of meteorological traffic especially on the routes between the collecting stations, and therefor, the scientific traffic which is also on the increase is dependent on the exchange via the channels arranged by the stations affected. Further improvement of telecommunications facilities and introduction of more efficient systems are requested in the near future. SCAR was invited and encouraged to continue their scientific and technical studies for overcoming the difficulties involved in the Antarctic telecommunications. However, the unreliability of H. F. radio communication in Antarctica may not be cleared out so far as those links are kept in operation by means of the ionospheric propagation, which is disturbed heavily by the effects known as the polar absorption or blackout. Most reliable and economical method in the future telecommunications in Antarctica will be the introduction of satellite relay network system, as the microwave route not the scattered wave link may not be applicable owing too much difficulties are expected in those field operations both on the construction and the maintenance. The output power of H. F. transmitter at Syowa Station will be ...